2014
DOI: 10.1073/pnas.1319193111
|View full text |Cite
|
Sign up to set email alerts
|

Unusually long-lived pause required for regulation of a Rho-dependent transcription terminator

Abstract: Up to half of all transcription termination events in bacteria rely on the RNA-dependent helicase Rho. However, the nucleic acid sequences that promote Rho-dependent termination remain poorly characterized. Defining the molecular determinants that confer Rho-dependent termination is especially important for understanding how such terminators can be regulated in response to specific signals. Here, we identify an extraordinarily long-lived pause at the site where Rho terminates transcription in the 5′-leader reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 63 publications
3
52
0
Order By: Relevance
“…The explanation may lie with pleiotropic effects. RNAP mutants have the capacity to affect the expression of every gene, but rho influences termination in a subset of 20-50% of E. coli genes (42,43). Because rpoB has the potential for more pleiotropic interactions, it likely also has a higher probability to generate fitness tradeoffs via antagonistic pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation may lie with pleiotropic effects. RNAP mutants have the capacity to affect the expression of every gene, but rho influences termination in a subset of 20-50% of E. coli genes (42,43). Because rpoB has the potential for more pleiotropic interactions, it likely also has a higher probability to generate fitness tradeoffs via antagonistic pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of Rho-dependent termination by riboswitches was described for the Mg 2+ -sensing mgtA riboswitch from Salmonella enterica (Hollands et al, 2012(Hollands et al, , 2014 for the flavin mononucleotide-sensing ribB riboswitch from E. coli (Hollands et al, 2012) and flavin mononucleotide riboswitch from the Gram-positive Corynebacterium glutamicum (Takemoto et al, 2015). In general, depending on the ligand concentration (e.g.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
“…The significance of riboswitch function lies in the transduction of ligand binding into changes in expression of the downstream gene. Recently, it was shown that some riboswitches use Rho to attenuate transcription, thus linking Rho to the process of sensing and regulating gene expression in response to environmental cues (Proshkin et al, 2014).Regulation of Rho-dependent termination by riboswitches was described for the Mg 2+ -sensing mgtA riboswitch from Salmonella enterica (Hollands et al, 2012(Hollands et al, , 2014 for the flavin mononucleotide-sensing ribB riboswitch from E. coli (Hollands et al, 2012) and flavin mononucleotide riboswitch from the Gram-positive Corynebacterium glutamicum (Takemoto et al, 2015). In general, depending on the ligand concentration (e.g.…”
mentioning
confidence: 99%
“…When this happens, the mgtA leader mRNA adopts a conformation that advances transcription elongation into the mgtA coding region. By contrast, when cytosolic Mg 2+ remains high, the conformation of the mgtA leader mRNA promotes transcription termination within the leader by the Rho protein [80,81]. …”
Section: Introductionmentioning
confidence: 99%